Solutions for a fractional diffusion equation: Anomalous diffusion and adsorption–desorption processes - E.K. Lenzi; M.A.F. dos Santos; M.K. Lenzi; D.S. Vieira; L.R. da Silva (Journal of King Saud University: Science, 2016)
We investigate the solutions for a fractional diffusion equation subjected to boundary conditions which can be connected to adsorption–desorption processes. The analytical solutions were obtained using the Green function approach and showed an anomalous spreading which can be connected to an anomalous diffusion.